Efektivitas Promosi Pantai Tlangoh Kabupaten Bangkalan Melalui Sosial Media - Hera Wahyuni (Journal of Social, Culture, and Language, 2024)
Social media is the main attraction for attracting tourists and providing various available information, as well as answering various curiosities. The role of ICT in the world of tourism as facilities and infrastructure in promoting tourism which we often hear electronically is called digital marketing. Social media marketing or digital marketing is one of the strategies implemented in marketing tourism products in the current era. The existence of digital marketing makes someone's interest in traveling even higher. Based on this, it encourages researchers to conduct research related to strategies for using digital technology as a medium for conveying information in carrying out promotions, building preferences, and increasing visitors to Tlangoh beach in Bangkalan district. The aim of this research is: To determine the effectiveness of social media in promoting Tlangoh beach tourism in Bangkalan Regency. This research uses qualitative methods with the AISAS model (Attention, Interest, Search, Action, Share). Data analysis in this research uses a search for calculating the mean (average), percentage, and mode or response that often appears in the questionnaire results. AISAS is the process of a consumer paying attention to a product, service or advertisement (Attention) and generating interest (Interest) so that there is a desire to collect information (Search) about the item. Apart from that, researchers also observed the development of Tlangoh beach promotional social media such as Instagram and Facebook. So this research is included in the type of descriptive study. The results of this research explain that the 5 AISAS measurement dimensions (Attention, Interest, Search, Action, Share) reveal that the share dimension provides the highest contribution related to the promotion of Tlangoh beach tourism in Bangkalan. This shows that visitors want to tell stories about their experiences of visiting Tlangoh Beach tourism to friends/colleagues, either directly or digitally, such as on social media they have.Keywords: social media, Tangoh beach, Bangkalan